1936
DOI: 10.1021/ja01296a047
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Equilibria of Sodium Sulfate at Temperatures from 150 to 350°. II. Effect of Sodium Hydroxide and Sodium Carbonate1

Abstract: been found that the presence of dissolved solid has a marked effect in reducing the expansion of water as the critical temperature is approached, (1) Published by permission of the Director, U. S. Bureau of Mines.(Not subject to copyright.) (2) Research chemical engineer, Joint Research Committee on Boiler Feed-Water Studies, attached to Nonmetallic Minerals Experiment Station, U. S. Bureau of Mines, Rutgers University, New Brunswick, N. J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1937
1937
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Other solid species that can form from this system at temperatures above 100 °C include sodium carbonate, sodium carbonate monohydrate, and sodium sulfate. 2,3 It is interesting to note that the experimental procedures followed by the researchers cited above achieved apparent equilibrium by adding excess amounts of sodium carbonate and sodium sulfate crystals to solutions of these solutes. The primary concern with this approach is that it might have extended the domains of sodium carbonate and sodium sulfate if the system had not reached equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Other solid species that can form from this system at temperatures above 100 °C include sodium carbonate, sodium carbonate monohydrate, and sodium sulfate. 2,3 It is interesting to note that the experimental procedures followed by the researchers cited above achieved apparent equilibrium by adding excess amounts of sodium carbonate and sodium sulfate crystals to solutions of these solutes. The primary concern with this approach is that it might have extended the domains of sodium carbonate and sodium sulfate if the system had not reached equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…The first three papers of this series have presented data for the solubility of sodium sulfate in solutions containing sodium hydroxide, sodium chloride, sodium carbonate and sodium phosphate at temperatures above 100°. [6][7] The utility of this information should be increased materially by the determination of the degree of accuracy with which the equilibrium values can be applied to a system undergoing evaporation. In this paper comparison is made between the amount of sodium sulfate in a solution from which steam is being removed, and the amount of sodium sulfate present in the same solution at equilibrium.…”
Section: Effect Of Sodium Hydroxide On the Systemmentioning
confidence: 99%
“…The operation of the bomb was essentially as described in the first paper of this series. 6 Solubility of Sodium Phosphate in Water and Sodium Hydroxide Solutions Mulder7 and Apfel8 have shown that the solubility of trisodium phosphate in water increases rapidly with temperature from 0 to above 100°. Above 25°Mulder's values as shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have been done on the solubility for the subsystems of the five-component system Na 2 CO 3 + NaHCO 3 + Na 2 SO 4 + NaCl + H 2 O at 150 °C (Eddy and Menzies, 1940;Itkina and Kohova, 1955;Palkova and Ahumov, 1962;Schroeder et al, 1935Schroeder et al, , 1936Stephen and Stephen, 1979;Waldeck et al, 1934;Zhang et al, 1991), but the studies of the phase equilibria for the ternary systems NaHCO 3 + NaCl + H 2 O and NaHCO 3 + Na 2 SO 4 + H 2 O, the quaternary systems Na 2 CO 3 + NaHCO 3 + Na 2 SO 4 + H 2 O, Na 2 CO 3 + NaHCO 3 + NaCl + H 2 O, and NaHCO 3 + Na 2 SO 4 + NaCl + H 2 O, and the five-component system Na 2 CO 3 + NaHCO 3 + Na 2 SO 4 + NaCl + H 2 O at 150 °C have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%